Second Language Corner for Children’s House: A Practitioner–Researcher Journey Into Bilingualism in Montessori Education - Rosales Chavarria, Romali (Journal of Montessori Research, 2021)
This work reports, from a qualitative research perspective, the development of an English Corner project for a preschool Children’s House classroom in central Mexico over the course of a 3-year period. It shows the transition of a language specialist over six consecutive periods of work, from a traditional understanding and practice of teaching English as a second language to young learners into a more comprehensive one of the Montessori Method. The analysis of my own practice is used to recover insights through a reflective process with the intention to develop a second language (L2) Montessori program for 3- to 6-year-olds that aligns better with Montessori pedagogy.  Variables such as instruction time, setting, group constitution, materials, and teaching and learning strategies allowed for certain aspects to arise as leading points of interest for the focus of the analysis and the methodological and pedagogical adaptations that followed each period. This paper is an attempt to fill the gap between the need to deliver a second language effectively in Montessori education and the lack of guidance for doing it the Montessori way; it is especially for practitioners who do not have a Montessori background but also for Montessori-trained teachers for whom more specific preparation would aid their practice. I also hope to stimulate further research in the field of second language acquisition and multilingualism in Montessori education at every level of education.